Receptor Binding for the Entry Mechanisms of SARS-CoV-2: Insights from the Original Strain and Emerging Variants - Mohamed Mahdi; Irene Wanjiru Kiarie; János András Mótyán; Gyula Hoffka; Aya Shamal Al-Muffti; Attila Tóth; József Tőzsér (Viruses)
Since its emergence in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has continuously evolved, giving rise to multiple variants that have significantly altered the trajectory of the COVID-19 pandemic. These variants have resulted in multiple waves of the pandemic, exhibiting characteristic mutations in the spike (S) protein that may have affected receptor interaction, tissue tropism, and cell entry mechanisms. While the virus was shown to primarily utilize the angiotensin-converting enzyme 2 (ACE2) receptor and host proteases such as transmembrane serine protease 2 (TMPRSS2) for entry into host cells, alterations in the S protein have resulted in changes to receptor binding affinity and use of alternative receptors, potentially expanding the virus’s ability to infect different cell types or tissues, contributing to shifts in clinical presentation. These changes have been linked to variations in disease severity, the emergence of new clinical manifestations, and altered transmission dynamics. In this paper, we overview the evolving receptor utilization strategies of SARS-CoV-2, focusing on how mutations in the S protein may have influenced viral entry mechanisms and clinical outcomes across the ongoing pandemic waves.